Therapeutic Communication Management at Permata Bunda Hospital, Medan - Syahputra, Helmi; Kholil, Syukur; Lubis, Suwardi (Budapest International Research and Critics University, 2020)
This study aims to find out therapeutic communication management at Permata Bunda Hospital, Medan. This type of research is qualitative research. This research is conducted at Permata Bunda Hospital, Medan. The result shows that In the application in the therapeutic communication management environment that is carried out by Permata Bunda Medan Hospital, it includes: what activities will be achieved, how to implement them, with whom the implementation will be carried out, when to implement them, where and with what budget, types of activities to be carried out, duration of activities - these activities will take place, the costs of implementing those activities are provided, the income that the hospital will receive.